2012
DOI: 10.1073/pnas.1218348109
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug binding properties of the AcrB efflux pump characterized by molecular dynamics simulations

Abstract: Multidrug resistance in Gram-negative bacteria, to which multidrug efflux pumps such as the AcrB transporter makes a major contribution, is becoming a major public health problem. Unfortunately only a few compounds have been cocrystallized with AcrB, and thus computational approaches are essential in elucidating the interaction between diverse ligands and the pump protein. We used molecular dynamics simulation to examine the binding of nine substrates, two inhibitors, and two nonsubstrates to the distal bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
337
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 213 publications
(363 citation statements)
references
References 45 publications
18
337
0
2
Order By: Relevance
“…Side chains of other most relevant residues are shown with thinner sticks, colored by residue type and red in wild type and G288D, respectively. The orientation of CIP is derived from the MD simulations (27), and that of DOXO is based on the experimental X-ray structure as from PDB ID code 4DX7 (22). Lines denote values, for strains carrying the G288D mutation, which are significantly different to the strain carrying the wild-type AcrB.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Side chains of other most relevant residues are shown with thinner sticks, colored by residue type and red in wild type and G288D, respectively. The orientation of CIP is derived from the MD simulations (27), and that of DOXO is based on the experimental X-ray structure as from PDB ID code 4DX7 (22). Lines denote values, for strains carrying the G288D mutation, which are significantly different to the strain carrying the wild-type AcrB.…”
Section: Discussionmentioning
confidence: 99%
“…Because this site has been shown to be extremely adaptable to many substrates (27), it cannot be ruled out that despite the large effect due to G288D substitution the pocket would still be able to accommodate most compounds but with altered affinities. In agreement with such an interpretation we observed that the G288D substitution caused an increase in intracellular accumulation of doxorubicin and minocycline, which have been reported to bind to the phenylalanine cluster in the distal binding pocket (2), and concomitant increased susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations